2021
DOI: 10.1007/s00404-021-06146-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fetal presentation on neurodevelopmental outcome in a trial of preterm vaginal delivery: a nationwide, population-based record linkage study

Abstract: Purpose To assess the risk of adverse neurodevelopmental outcomes at the age of four after an attempted vaginal delivery according to the fetal presentation in birth. Methods This retrospective record linkage study evaluated the risks of cerebral palsy, epilepsy, intellectual disability, autism spectrum disorder, attention-deficit/hyperactivity disorder, and speech, visual, and auditory disabilities among preterm children born after an attempted vaginal br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…among extremely pre-term and very pre-term infants with breech presentation; however, among moderate to late pre-term births, breech was associated with an increased risk of ASD compared to children with vertex presentation 52. However, because of the low prevalence of pre-term, breech presentation and ASD, the results of this and most studies have been very imprecise and should be interpreted with caution.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…among extremely pre-term and very pre-term infants with breech presentation; however, among moderate to late pre-term births, breech was associated with an increased risk of ASD compared to children with vertex presentation 52. However, because of the low prevalence of pre-term, breech presentation and ASD, the results of this and most studies have been very imprecise and should be interpreted with caution.…”
mentioning
confidence: 75%
“…While this study does not explore the underlying biology, we hypothesised that malpresentation among term infants may reflect delays in turning associated with early neurodevelopmental differences that later manifest as ASD. A study of vaginal breech delivery that used detailed data from the Finland Medical Birth Register and the Hospital Discharge Register reported no increase in risk of neurodevelopmental outcomes among extremely pre‐term and very pre‐term infants with breech presentation; however, among moderate to late pre‐term births, breech was associated with an increased risk of ASD compared to children with vertex presentation 52 . However, because of the low prevalence of pre‐term, breech presentation and ASD, the results of this and most studies have been very imprecise and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CS delivery has been supported by studies showing improved survival with less morbidity when compared to vaginal delivery [50]. However, such improvement in VLBW outcomes with the mode of delivery was not consistent and other studies showed no difference in outcomes based on the mode of delivery [48,51]. The CS delivery rate for macrosomic neonates was almost double that observed in NBW neonates, which is consistent with findings from studies both from Saudi Arabia [33] and other countries [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The adverse pregnancy outcomes (APOs) that we will focus on in this work -including early gestational age (GA) at delivery (a continuous surrogate for preterm birth), gestational diabetes, severe preeclampsia (severe pree), or preeclampsia superimposed on hypertension (superimposed pree) -are associated with severe short-and long-term consequences for both the mother and infant (1)(2)(3)(4), underscoring the importance of management and prevention (5)(6)(7)(8)(9). Currently, however, highly efficacious therapeutic options to prevent APOs are lacking, highlighting the critical clinical need to identify actionable risk targets and prevent their development (10).…”
Section: Introductionmentioning
confidence: 99%